Toward a new start: Approaches to a strategic partnership between NATO and Russia - Margarete Klein (Stiftung Wissenschaft und Politik (SWP), 2010)
Following the war in Georgia in the summer of 2008, relations between Russia and NATO were on hold for some time. But now NATO Secretary General Anders Fogh Rasmussen has announced a new beginning. During his inaugural visit to Moscow, Rasmussen said his goal was to establish a 'true strategic partnership' with Russia. But that will require more than just a return to business as usual. The NATO-Russia Council (NRC) has so far proved unable to transform the relationship - which currently fluctuates between selective cooperation and outright competition - into a more substantial partnership. This would require overcoming fundamental differences of opinion, particularly with respect to the basic elements of the international political order in Europe and the post-Soviet region
Keywords: 320